A case report of phosphaturic mesenchymal tumor-induced osteomalacia. Issue 51 (December 2017) - Wu, Weiqian; Wang, Chongyang; Ruan, Jianwei; Chen, Feng; Li, Ningjun; Chen, Fanghu
Abstract: Rationale: Tumor-induced osteomalacia (TIO) is a rare and often misdiagnosed syndrome. Surgical resection is currently the first line treatment for TIO. Patient concerns: Here we report the case of a 49-year-old woman presented with intermittent pain in the right chest and bilateral hip that had persisted for over two years. Diagnoses: She was diagnosed of TIO caused by a phosphaturic mesenchymal tumor based on the following examinations. Laboratory tests revealed high serum alkaline phosphatase, high urinary phosphorus, hypophosphatemia and normal serum calcium levels. 18-FDG PET/CT indicated a systemic multi-site symmetrical pseudo fracture and a tumor in the 7th right rib. Interventions: Curettage of the tumor was performed, and pathological analysis also confirmed our diagnoses as a phosphaturic mesenchymal tumor. Outcomes: At seven months post-surgery, the symptoms were relieved, proximal muscle strength was improved and serum levels of phosphorus and alkaline phosphatase normalized. The bilateral femoral neck and bilateral pubic bone fractures were blurred in the pelvic plain X-ray, suggesting that the fracture was healing. Lessons: This case report strengthened the importance of recognition of this rare disease to avoid delay of diagnosis and surgical removal of the causative tumor is recommended.